The Woman Migrant – Between Tradition and Modernity - Knežević, Snežana; Momčilov, Milkica (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
The focus of this work is on women migrants who have found temporary refuge on the migrant route in the Republic of Serbia, specifically in the shelter-transit center in Kikinda. The population of migrants that is moving towards countries of Western Europe as their final destination faces many problems along the way, especially women, who are exposed to a high level of risk. The authors of this work deal with the position of those women, exploring (by method of in-depth interviews) if, and in which way, it has changed with their arrival in shelters in the Republic of Serbia. Likewise, the work investigates what the response of institutions and organizations is to the needs of the migrants, as well as whether they recognize the importance of providing specialized services for women. Based on the analysis of the received answers, and relying on the international and national legal framework, suggestions are made for the amelioration of the position of women migrants in the Republic of Serbia.